Relationship between anterior disc displacement with/without reduction and effusion in temporomandibular disorder patients using magnetic resonance imaging - Koh, Kwang-Joon; Park, Ha-Na; Kim, Kyoung-A (Imaging science in dentistry, 2013)
This study was performed to evaluate the relationship between anterior disc displacement and effusion in temporomandibular disorder (TMD) patients using magnetic resonance imaging (MRI). The study subjects included 253 TMD patients. MRI examinations were performed using a 1.5 T MRI scanner. T1- and T2-weighted images with para-sagittal and para-coronal images were obtained. According to the MRI findings, temporomandibular joint (TMJ) disc positions were divided into 3 subgroups: normal, anterior disc displacement with reduction (DWR), and anterior disc displacement without reduction (DWOR). The cases of effusion were divided into 4 groups: normal, mild (E1), moderate (E2), and marked effusion (E3). Statistical analysis was made by the Fisher's exact test using SPSS (version 12.0, SPSS Inc., Chicago, IL, USA). The subjects consisted of 62 males and 191 females with a mean age of 28.5 years. Of the 253 patients, T1- and T2-weighted images revealed 34 (13.4%) normal, DWR in 103 (40.7%), and DWOR in 116 (45.9%) on the right side and 37 (14.6%) normal, DWR in 94 (37.2%), and DWOR in 122 (48.2%) joints on the left side. Also, T2-images revealed 82 (32.4%) normal, 78 (30.8%) E1, 51 (20.2%) E2, and 42 (16.6%) E3 joints on the right side and 79 (31.2%) normal, 85 (33.6%) E1, 57 (22.5%) E2, and 32 (12.7%) E3 on the left side. There was no difference between the right and left side. Anterior disc displacement was not related to the MRI findings of effusion in TMD patients (P>0.05).